Quantification of blood flow in brain tumors: comparison of arterial spin labeling and dynamic susceptibility-weighted contrast-enhanced MR imaging - Warmuth, Carsten; Gunther, Matthias; Zimmer, Claus (Radiology, 2003)
To implement an arterial spin labeling technique that is feasible in routine examinations and to test the method and compare it with dynamic susceptibility-weighted contrast material-enhanced magnetic resonance (MR) imaging for evaluation of tumor blood flow (TBF) in patients with brain tumors. Thirty-six patients with histologically proven brain tumors were examined at 1.5 T. A second version of quantitative imaging of perfusion by using a single subtraction with addition of thin-section periodic saturation after inversion and a time delay (Q2TIPS) technique of pulsed arterial spin labeling in the multisection mode was implemented. After arterial spin labeling, a combined T2- and T2*-weighted first-pass bolus perfusion study (gadopentetate dimeglumine, 0.2 mmol/kg) was performed by using a double-echo echo-planar imaging sequence. In regions of interest, maps of absolute and relative cerebral blood flow were computed and analyzed with arterial spin labeling and dynamic susceptibility-weighted contrast-enhanced MR imaging, respectively. Both techniques yielded the highest perfusion values in imaging of glioblastomas and the lowest values in imaging of two low-grade gliomas that both showed strong gadopentetate dimeglumine enhancement. There was a close linear correlation between dynamic susceptibility-weighted contrast-enhanced MR imaging and arterial spin labeling in the tumor region of interest (linear regression coefficient, R = 0.83; P <.005). Blood flow is underestimated with arterial spin labeling at low flow rates. High- and low-grade gliomas can be distinguished at the same level of significance with both methods. Absolute TBF is less important for tumor grading than is the ratio of TBF to age-dependent mean brain perfusion. Arterial spin labeling is a suitable method for assessment of microvascular perfusion and allows distinction between high- and low-grade gliomas.